2022
DOI: 10.21203/rs.3.rs-2036751/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Placental mesenchymal stem cells ameliorate NLRP3 inflammasome induced ovarian insufficiency by modulating macrophage M2 polarization

Abstract: Background: Premature ovarian insufficiency (POI) is a common clinical problem but there are currently no effective therapies. Pyroptosis induced by the NLRP3 inflammasome is considered a possible mechanism of POI. Placental mesenchymal stem cells(PMSCs) have excellent immunomodulatory potential and offer a promising method for treating POI. Methods: Female Sprague–Dawley rats were randomly divided into four treatment groups: control (no POI), POI with no PMSCs, POI with PMSCs transplant, and POI with hormones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This condition not only compromises the integrity of the membranes but also exerts an impact on the body’s immune system. [23] In the context of genital tract infection, inflammation can trigger the production of various protein molecules that actively participate in the immune mechanisms of placental membrane tissues. [24] According to a prior study, [25] IL-1 has been identified as an inducer of matrix metalloproteinases (MMPs), and MMPs play a pivotal role in the metabolism of extracellular matrix proteins within fetal membrane tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This condition not only compromises the integrity of the membranes but also exerts an impact on the body’s immune system. [23] In the context of genital tract infection, inflammation can trigger the production of various protein molecules that actively participate in the immune mechanisms of placental membrane tissues. [24] According to a prior study, [25] IL-1 has been identified as an inducer of matrix metalloproteinases (MMPs), and MMPs play a pivotal role in the metabolism of extracellular matrix proteins within fetal membrane tissues.…”
Section: Discussionmentioning
confidence: 99%